Design of a novel nautilus bionic flow field for proton exchange membrane fuel cell by analyzing performance. (January 2023) - Li, Nan; Wang, Wanteng; Xu, Ruiyang; Zhang, Jinhui; Xu, Hongpeng
Highlights: A bionic flow channel based on the nautilus structure is proposed. Performance of nautilus channel is better than that of serpentine channel. The 5 annular nautilus channel have the best all-around performance. Abstract: Bionic flow channels have wide applications in proton-exchange membrane fuel cells (PEMFCs), especially at the cathode, significantly improving their performance. This study proposed a bionic flow channel based on the internal structure of the nautilus. A three-dimensional (3D) single-phase isothermal CFD model was established for a multi-physical field numerical simulation. The air inlet was located in the centre of the channel, and the reactants from the flow channel in the centre passed through the arched flow channel to the surrounding annular flow channel. In this study, traditional serpentine, honeycomb-like, and nautilus bionic flow channels were investigated. The nautilus bionic flow channel was shown to have more uniform reactants, better water removal, lower concentration polarisation loss, and better power compared to the other two flow channels. Compared to the serpentine flow channel, the peak current density increased by 46.7%, and the peak power density increased by 21.53%. Compared with the honeycomb-like flow channel, the peak current density increased by 5.73%, and the power densities were similar. The nautilus bionic flow channel had better reactant uniformity, current density, and water removal compared to the honeycomb-like flow channel. In addition, this study investigated the superiority of the nautilus bionic flow channel over the serpentine flow channel under different cathode air inlet flow velocities and the effect of different numbers of annular flow channels on the nautilus bionic flow channel, with the results indicating that the performance of five annular flow channels was best. Graphical abstract: Image, graphical abstract